The Level of Acetic Acid Poisoning as an Indicator of a Healthy Lifestyle (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
In our century, despite the growth of media and other social networks in the age of high information technology, the problems caused by the consequences of poisoning with acetic acid, which is better known as table vinegar, is widely used in cooking, as well as in everyday life for various purposes, from preserving food to cleaning, are still relevant. Despite its widespread use, acetic acid in high concentrations is a dangerous chemical, and cases of poisoning with it can become a serious threat to health.